Solving difficult problems creatively: a role for energy optimised deterministic/stochastic hybrid computing - Palmer, Tim N.; O’Shea, Michael (Frontiers in Computational Neuroscience, 2015)
How is the brain configured for creativity? What is the computational substrate for ‘eureka’ moments of insight? Here we argue that creative thinking arises ultimately from a synergy between low-energy stochastic and energy-intensive deterministic processing, and is a by-product of a nervous system whose signal-processing capability per unit of available energy has become highly energy optimised. We suggest that the stochastic component has its origin in thermal noise affecting the activity of neurons. Without this component, deterministic computational models of the brain are incomplete.